Tailing and axisymmetric static laser beam shapes to steer microstructure and improve mechanical properties of autogenously laser welded AA6082 alloy - Venkat Vivek Pamarthi; Tianzhu Sun; Abhishek Das; Qamar Hayat; Alexander Griffiths; Lewis Johnson; Pasquale Franciosa (Materials & Design)
Laser beam shaping technology has advanced remote laser welding applications, yet welding AA6xxx alloys remains challenging due to their sensitivity to cracking. Recent studies on these alloys have focussed on axisymmetric shapes, with a limited understanding of molten flow dynamics and microstructural evolution in the context of non-axisymmetric shapes. This study examines the impact of tailing and axisymmetric laser beam shapes on steering microstructure, and cracking mitigation in AA6082 alloy by combining multiphysics CFD simulation and experimental observations. Two sets of beam shapes were investigated: (1) four axisymmetric core-to-ring beam shapes with varying ring diameter, and power, and (2) a tailing beam shape with a 3 mm elongated tail. The findings indicate that introducing a 580 µm ring to the core beam reduces crack formation by lowering thermal gradients; however, increasing the power of the ring beam at a constant diameter, coarsens the microstructure, producing axial columnar grains with higher crack sensitivity. Expanding the ring beam diameter to 1200 µm reduced molten flow and thermal gradients, resulting in decreased cracking and increased tensile strength by 36%, compared to the core-only shape. The tailing shape beam further lowered thermal gradients owing to the larger molten pool and elongated tail, achieving a 62% grain size reduction compared to the core-only shape.